Modelling Shared Assets in Indonesia’s Forfeiture Bill: International Collaboration and Digital Networks - Bayu Sujadmiko; Rohaini Rohaini; Nobuhide Otomo; Ikhsan Setiawan; Nurul Azizah (Lex Scientia Law Review, 2025)
Article 54, paragraph 3, of the UN Convention Against Corruption (UNCAC) encourages countries to implement efforts to confiscate assets resulting from crimes committed without a criminal conviction, often known as in rem. Indonesia is one of the countries that ratified the UNCAC with Law No. 7 of 2006. Further implementation of in rem forfeiture is outlined in the Asset Forfeiture Bill, which regulates the mechanism for in rem forfeiture of assets in detail. The bill also regulates asset sharing, previously only accommodated by Article 57 of Law No. 1 of 2006 concerning Mutual Assistance. Aside from being a solution to overcoming the cost of forfeiture, which tends to be large, asset sharing is also intended to prevent the interference of other forces that cause the forfeiture process not to run effectively. This mechanism also precludes different parties from sharing burdens and benefits (a win-win solution). Asset sharing is practiced in some countries, such as the United States, Switzerland, and Canada.